Population dynamics of rice leaffolders (Lepidoptera: Pyralidae) and their natural enemies in irrigated rice in the Philippines - Kraker, J. de.; Huis, A. van; Heong, K.L.; van Lenteren, J.C.; Rabbinge, R. (Cambridge University Press, 1999)
Populations of rice leaffolders and their natural enemies were studied in eight crops of irrigated rice in Laguna Province, the Philippines. The rice leaffolder complex consisted of three species: Cnaphalocrocis medinalis (Guenée), Marasmia patnalis Bradley and M. exigua Butler. Leaffolder population dynamics were characterized by an egg peak at maximum tillering and a broad larval peak around booting stage. Peak densities ranged from 0.2 to 2.0 larvae per hill. Most larvae originated from immigrant moths and there was no substantial second generation. The seasonal percentage egg parasitism by Trichogramma sp. ranged from 0 to 27%, and percentage larval parasitism from 14 to 56%. The braconid Macrocentrus philippinensis Ashmead was the most commonly reared larval parasitoid. Forty natural enemy taxa that may attack rice leaffolders were identified from suction and sweepnet samples: 24 predator taxa and 16 parasitoid taxa. The estimated survival rates from leaffolder egg to larval stages and between larval stages showed large variation between rice crops, but were not clearly correlated with observed levels of parasitism, natural enemy abundance, or natural enemy to leaffolder ratios. It is suggested that the generally low densities of rice leaffolders in Philippine transplanted rice are caused by their ovipositional preference for crops at the maximum tillering stage, allowing for only one generation, and by high immature mortality caused by the abundant and diverse complex of natural enemies.